Influence of chronic cadmium exposure on the tissue distribution of copper and zinc and oxidative stress parameters in rats. (August 2016) - Erdem, Onur; Yazihan, Nuray; Kocak, Mehtap Kacar; Sayal, Ahmet; Akcil, Ethem
The aim of this study was to investigate the effect of oral cadmium (Cd) intoxication on the antioxidant response and its relationship with essential bioelements like copper (Cu) and zinc (Zn). The experimental group was chronically exposed to Cd daily for 8 weeks via consumption of water containing 15 ppm cadmium chloride. Cu, Zn, and Cd concentrations and oxidative stress parameters were analyzed in liver, kidney, and heart tissues. Exposure to Cd led to a significant decrease in the activities of superoxide dismutase in all considered samples while a significant increase in the activity of glutathione peroxidase except for the kidney. We found a significant increase in malondialdehyde concentration in the tissues except for heart. Also oral administration of Cd caused a significant reduction of Zn and Cu in the tissues. Our results allow us to hypothesize that higher Cd concentration in the tissues causes oxidative stress by increasing malondialdehyde as a means of altering antioxidant defense system and deterioration of bioelements in rat liver, kidney, and heart. In addition, further studies are needed to explain the effect of long-term, low-dose exposure to Cd on distribution of bioelements and its relationship with oxidative stress.